Repetitive exercise dystonia: A difficult to treat hazard of runner and non-runner athletes. (June 2016) - Cutsforth-Gregory, Jeremy K.; Ahlskog, J. Eric; McKeon, Andrew; Burnett, Melinda S.; Matsumoto, Joseph Y.; Hassan, Anhar; Bower, James H.
Abstract: Introduction: Runner's dystonia has previously been described in small series or case reports as a lower limb, task-specific dystonia. We have occasionally encountered this disorder and recognized the same phenomenon in non-runners regularly engaging in lower limb exercise. We wished to characterize the syndrome further, including outcomes, treatment, and the diagnostic usefulness of electrophysiology. Methods: We conducted a retrospective review and follow-up survey of adults seen at Mayo Clinic (1996–2015) with task-specific dystonia arising after prolonged repetitive lower limb exercise. The findings were compared to all 21 previously reported cases of runner's dystonia. Results: We identified 20 patients with this condition, 13 runners and seven non-runner athletes. Median age at dystonia onset was in mid-adulthood. Correct diagnosis was delayed by a median of 3.5 years in runners and 1.6 years in non-runners, by which time more than one-third of patients had undergone unsuccessful invasive procedures. Most patients had dystonia onset in the distal lower limb. Dystonia was task-specific with exercise at onset but progressed to affect walking in most. Sensory tricks were reported in some. Surface EMG was consistent with task-specific dystonia in nine patients. Botulinum toxin, levodopa, clonazepam, trihexyphenidyl, and physical therapy provided modest benefit to some, but all patients remained substantially symptomatic at last follow up. Conclusions: Repetitive exercise dystonia is task-specific, confined to the lower limb and occasionally trunk musculature. It tends to be treatment-refractory and limits ability to exercise. Diagnosis is typically delayed, and unnecessary surgical procedures are common. Surface EMG may aid the diagnosis. Highlights: Repetitive exercise dystonia is task-specific, confined to lower limbs and trunk. Diagnosis is typically delayed, with unnecessary surgical procedures common. It is non-progressive but treatment-refractory and limits ability to exercise. Surface EMG may aid the diagnosis.